A ingestão de bebida açucarada altera o metabolismo e a resposta imune em camundongos C57BL/6 - Sara Cândida Barbosa (2021)
The intestine is the main surface for dietary absorption, and the immune compartments associated with it have a complex network of tolerogenic mechanisms capable of interacting constantly and simultaneously with nutrients and the microbiota without triggering pathological processes. Dietary nutrients are key to the differentiation of cells in the intestinal mucosa and to the integrity of the intestinal barrier. Eating habits related to high fat and refined food intake, as well as to low complex carbohydrates and fiber intake, favor the development of chronic non-communicable diseases and the worsening of inflammatory bowel diseases. Based on this evidence, we sought to clarify how the metabolic changes induced by sugary drinks interfere with the gut immune system and with the susceptibility to mucositis. C57BL/6 or C57BL/6-GFP-knock-in FoxP3 mice were fed with AIN93G diet and given water or a sugar-sweetened beverage containing 25% of a glucose and fructose mixture in a 45:55 ratio, respectively. After 8 weeks of continuous ingestion of the sugar-sweetened beverage, there was an increase in total calorie intake, which was able to cause body composition and metabolic changes related to metabolic syndrome. Such changes included elevated blood glucose, glycosuria and glycated hemoglobin, alteration in blood lipid profile, as well as adipose tissue accumulation and liver degeneration. Adipose tissue inflammation in the sugar-sweetened beverage group was identified by histological and flow cytometry analysis, which showed the presence of leukocytes around hypertrophied adipocytes and increased frequency of TCD4+RORγT+ cells, related to the TH17 profile, as well as reduced frequency of FoxP3+ regulatory T cells. Moreover, histological analysis of the ileum of mice that consumed excessive simple carbohydrates showed flattening of the villi and reduced numbers of goblet cells. When the cell frequency of the lymph node responsible for draining the distal portion of the small intestine was analyzed, a higher frequency of TH17 cells and a lower frequency of FoxP3+ regulatory T cells was observed. However, this inflammation was not enough to worsen mucositis caused by 5-FU. Therefore, metabolic syndrome associated with subclinical inflammation was identified in the distal portion of the small intestine of mice that chronically ingested the sugar-sweetened beverage.